sec(x) dy/dx = e^(y + sin(x)) So far I have : ln (secx) dy/dx = y + sin x ln (secx) dy = y + sinx dx Not sure what to do now... I don't think I can just subtract the y?
Follow Math Help Forum on Facebook and Google+
you should be able to solve this using implicit differentiation. so you have so then now just combine both function...
Originally Posted by veronicak5678 sec(x) dy/dx = e^(y + sin(x)) So far I have : ln (secx) dy/dx = y + sin x ln (secx) dy = y + sinx dx Not sure what to do now... I don't think I can just subtract the y? Note that Can you take it from here? --Chris
I see. Thanks!
Originally Posted by veronicak5678 I see. Thanks! , because in simplifying, I had , but Does this clarify things? --Chris
View Tag Cloud